Progress in plasma focus research at the Kurchatov Institute; Physica Scripta; Vol. 2014, № T161 - Krauz V.; Myalton V.; Vinogradov V.; Velikhov E.; Ananyev S.; Vinogradova Yu.; Dan'ko S.; Kalinin Yu.; Kanaev G. G. Gennady Grigorevich; Mitrofanov K.; Mokeev A.; Nashilevskiy A. V. Aleksandr Vladimirovich; et al. (2014, 2014)
Title screen